The sleeping giant. Project for the former Military Hospital in Naples - Federica Visconti; Renato Capozzi (Agathón)
The paper aims to describe a project developed under the scientific cooperation agreement between the Department for the Urban Planning and Territorial Management (UNESCO Site of the Municipality of Naples) and DiARC (Department of Architecture) of the ‘Federico II’ University of Naples. The project concerns a huge Convent Complex with an open courtyard typology, placed on the slope of the Sant’Elmo hill in Naples that is, today, abandoned. The aim is of re-introducing the Complex in the living dynamic of the city, through a careful work not only on the artefact in itself but also on its relationship with the city and landscape. Moreover, the project is the occasion to affirm a convinced choice of field about the theme of the intervention on the heritage, in favour of the culture of project and against an obstinate, as myopic, logic of conservation.